Effect of Intramammary Dry Cow Antimicrobial Treatment on Fresh Cow’s Milk Microbiota in California Commercial Dairies - Carl Basbas; Sharif Aly; Emmanuel Okello; Betsy M. Karle; Terry Lehenbauer; Deniece Williams; Erika Ganda; Martin Wiedmann; Richard V. Pereira (Antibiotics, 2022)
This study used 16S rRNA sequencing to evaluate the effects of dry cow antimicrobial therapy on the udder milk microbiota by comparing the microbial populations in milk at dry-off (DRY) (~60 days before calving) and post-partum (FRESH) (4–11 days after calving) from cows receiving an intramammary antibiotic infusion prior to dry-off (IMT) and cows that did not receive treatment (CTL). Milk was collected from 23 cows from the IMT group and 27 cows from the CTL group. IMT and DRY samples had a greater correlation with the genera Brevibacterium and Amaricoccus, and the family Micrococcaceae, when compared to IMT and FRESH samples. CTL group samples collected at DRY had a greater correlation with the genera Akkermansia and Syntrophus, when compared to FRESH samples; no bacterial taxa were observed to have a significant correlation with FRESH samples in the CTL group. DRY samples collected from the CTL group had a greater correlation with the genus Mogibacterium when compared to IMT and CTL samples. For DRY samples collected from the IMT group, a greater correlation with the genus Alkalibacterium when compared to DRY and CTL samples, was observed. The lack of a correlation for FRESH samples between the CTL and IMT treatment groups indicated that intramammary antimicrobial dry cow therapy had no significant effect on the udder milk microbiota post-partum.